Авторы номера - Нет (Мир России, 2013)
Vasiliy Anikin — Associate Professor, Chair for Social and Economic Systems and Social Policy, National Research University “Higher School of Economics”. Address: 20, Myasnitskaya St., Moscow, 101000, Russian Federation. E-mail: vasiliy.anikin@gmail.comGalina Bessokirnaya — Senior Research Fellow, Institute of Sociology (Russian Academy of Sciences). Address: Bldg. 5, 24/35, Krzhizhanovskogo St., Moscow, 117218, Russian Federation. E-mail: gala@isras.ruLyudmila Danilenko — Associate Professor, Pskov State University. Address: 2, Lenin Square, Pskov, 180760, Russian Federation. E-mail: daniluda@rambler.ruLiliya Ovcharova — Director, Centre for Analysis of Income and Living Standards of Population, National Research University “Higher School of Economics”. Address: 20, Myasnitskaya St., Moscow, 101000, Russian Federation. E-mail: l.ovcharova@hse.ruYuri Plusnin — Professor, Department of Public Administration, National Research University “Higher School of Economics”. Address: 20, Myasnitskaya St., Moscow, 101000, Russian Federation. E-mail: juri.plusnin@gmail.comEduard Ponarin — Professor, Chair for Methods and Technologies of Sociological Research, National Research University “Higher School of Economics”. Address: 20, Myasnitskaya St., Moscow, 101000, Russian Federation. E-mail: ponarin13@gmail.comDaria Popova — Leading Research Fellow, Centre for Analysis of Income and Living Standards, National Research University “Higher School of Economics”. Address: 20, Myasnitskaya St., Moscow, 101000, Russian Federation. E-mail: dpopova@hse.ruAlexandr Temnitskiy — Senior Research Fellow, Institute of Sociology (Russian Academy of Sciences). Address: Bldg. 5, 24/35, Krzhizhanovskogo St., Moscow, 117218, Russian Federation. E-mail: taleksandr@list.ruKirill Zhirkov — Senior Research Associate, Laboratory for Comparative Social Research, National Research University “Higher School of Economics”. Address: 20, Myasnitskaya St., Moscow, 101000, Russian Federation. E-mail: k.zhirkov@gmail.com